Accurate Modification Method of Gears Based on Spatial Lattice - Zhang Xiaodi; Li Gui; Liang Renjie; Ding Zixi; Peng Qinluan (Jixie chuandong)
Gear modification is an important technology in improving the meshing state, transmission accuracy and efficiency. However the existing modification methods and instrumental softwares are difficult to ensure the geometric quality and efficiency of gear modification. Therefore, a new gear modification method based on spatial lattice is proposed in this study. Firstly, according to the requirements of modification accuracy, the gear surface is discretized into regular spatial lattice, and the modification amount is mapped to the corresponding spatial point. The adjusted spatial lattice is then constructed into regular quadratic B-spline curves. Then, the modified gear surface is obtained by optimizing the mesh curve, and the new gear surface of the whole gear 3D model is updated adaptively. Finally, the method is seamlessly integrated into the 3D design software NX platform, and a gear accurate modification design system is developed. The result of the example shows that the method realizes the precise modification of the gear surface through the dual control of the modification position and the modification amount, and the high-quality gear profile surface is obtained, which improves the efficiency and practicality of the gear modification while ensuring the accuracy.